Systemic regulation of soybean nodulation and nitrogen fixation by nitrogen via isoflavones - Lyu, Xiaochen; Sun, Chunyan; Lin, Tao; Wang, Xuelai; Li, Sha; Zhao, Shuhong; Gong, Zhenping; Wei, Ziwei; Yan, Chao; Ma, Chunmei (Frontiers in Plant Science, 2022)
Nitrogen (N) inhibits soybean (Glycine max L.) nodulation and N2 fixation. Isoflavones secreted by soybean roots can stimulate signal transduction for symbiotic nodules, thus playing a key role in root nodule development and N2 fixation. The relationship between the inhibition of soybean nodulation, N2 fixation and isoflavones by N is still unclear. In this study, dual-root soybean plants were prepared by grafting, and N or isoflavones were supplied to unilateral roots. The number and dry weight of the soybean nodules, nitrogenase activity, isoflavone concentrations and relative changes in the level of expression of nodulation-related genes were measured to study the response relationship between the N systemic regulation the soybean nodule N2 fixation and changes in the concentrations of isoflavones in its roots. The results showed that N supply to one side of the dual-root soybeans systematically affected the N2 fixation of root nodules on both sides, and this effect began in the early stage of nodulation. Moreover, a unilateral supply of N systematically affected the concentrations of daidzein and genistein on both sides of the roots. The concentrations of isoflavones were consistent with the change trend of soybean root nodule and nodulation-related gene expression level. Treatment with unilateral N or isoflavones affected the soybean nodule N2 fixation and its nodulation-related genes, which had the same response to the changes in concentrations of root isoflavones. N regulates soybean nodulation and N2 fixation by systematically affecting the concentrations of isoflavones in the roots.